Responsibility to Protect dalam Kasus Genosida oleh ISIL terhadap Yazidi-Irak melalui Intervensi Militer Amerika Serikat - Putri, Dewi Agha; Sidik, Hasan (Jurnal ICMES, 2020)
This article aims to explain the military intervention carried out by the United States in response to the genocide carried out by the Islamic State of Iraq and the Levant (ISIL) against Yazidi community in Iraq. The researchers use the concept of Responsibility to Protect (R2P), which refers to a report from the International Commission on Intervention and State Sovereignty to see the procedure for procuring military intervention in the R2P framework in detail. This article found that besides several collateral damages, military intervention carried out by the United States was following the procedures set out by the International Commission on Intervention and State Sovereignty. The United States’ intervention was done by the Iraqi government's approval, which had previously requested assistance from the United States. This intervention can be seen as Iraqi collective self-defense as stated in Article 51 of the Charter of the United Nations or intervention based on approval as stipulated in Article 20 of the Responsibility of States for International Wrongful Acts 2001. This research was conducted qualitatively using sources in the form of a variety of documents and mass media reports.